The Safety and Efficacy of Lansoprazole plus Metoclopramide among Neonates with Gastroesophageal Reflux Disease Resistant to Conservative Therapy and Monotherapy: A Clinical Trial - Peymaneh Alizadeh Taheri; Elahe Validad; Kambiz Eftekhari (International Journal of Pediatrics)
Background. Gastroesophageal reflux disease (GERD) is one of the most common problems in neonates. The main clinical manifestations of neonatal GERD are frequent regurgitation or vomiting associated with irritability, crying, anorexia or feeding refusal, failure to thrive, arching of the back, and sleep disturbance. Aims. The efficacy and safety of ranitidine plus metoclopramide and lansoprazole plus metoclopramide in reducing clinical GERD symptoms based on I-GERQ-R scores in neonatal GERD resistant to conservative and monotherapy. Study Design. This study was a randomized clinical trial of term neonates with GERD diagnosis (according to the final version of the I-GERQ-R), resistant to conservative and monotherapy admitted to Bahrami Children Hospital during 2017-2019. Totally, 120 term neonates (mean age 10.91±7.17 days; girls 54.63%) were randomly assigned to a double-blind trial with either oral ranitidine plus metoclopramide (group A) or oral lansoprazole plus metoclopramide (group B). The changes of the symptoms and signs were recorded after one week and one month. At the end, fifty-four neonates in each group completed the study and their data were analyzed. Results. There was no significant difference in demographic and baseline characteristics between the two groups. The response rate of “lansoprazole plus metoclopramide” was significantly higher than “ranitidine plus metoclopramide” (7.44±3.86 score vs. 9.3±4.57 score, p=0.018) after one week and (2.41±3.06 score vs. 4.5±4.12 score, p=0.003) after one month (primary outcome). There were no drug adverse effects in either group during intervention (secondary outcome). Conclusions. The response rate was significant in each group after one week and one month of treatment, but it was significantly higher in the “lansoprazole plus metoclopramide” group compared with the “ranitidine plus metoclopramide” group. The combination of each acid suppressant with metoclopramide led to a higher response rate in comparison with monotherapy used before intervention. This study has been registered at the Iranian Registry of Clinical Trails (RCT20160827029535N3).